Transmission of Curing Light through Moist, Air-Dried, and EDTA Treated Dentine and Enamel - Uusitalo E; Varrela J; Lassila L; Vallittu PK (HINDAWI PUBLISHING CORP, 2026)
Objective. This study measured light transmission through enamel and dentin and the effect of exposed dentinal tubules to light propagation. Methods. Light attenuation through enamel and dentin layers of various thicknesses (1 mm, 2 mm, 3 mm, and 4 mm) was measured using specimens that were (1) moist and (2) air-dried (n = 5). Measurements were repeated after the specimens were treated with EDTA. Specimens were transilluminated with a light curing unit (maximum power output 1869 mW/cm(2)), and the mean irradiance power of transmitting light was measured. The transmission of light through teeth was studied using 10 extracted intact human incisors and premolars. Results. Transmitted light irradiance through 1 mm thick moist discs was 500 mW/cm(2) for enamel and 398 mW/cm(2) for dentin (p < 0.05). The increase of the specimen thickness decreased light transmission in all groups (p < 0.005), and moist specimens attenuated light less than air-dried specimens in all thicknesses (p < 0.05). EDTA treatment increased light transmission from 398 mW/cm(2) to 439 mW/cm(2) (1 mm dentin specimen thickness) (p < 0.05). Light transmission through intact premolar was 6.2 mW/cm(2) (average thickness 8.2 mm) and through incisor was 37.6 mW/cm(2) (average thickness 5.6 mm). Conclusion. Light transmission through enamel is greater than that through dentin, probably reflecting differences in refractive indices and extinction coefficients. Light transmission through enamel, dentin, and extracted teeth seemed to follow Beer-Lambert's law.